Теплофізичні особливості отримання об'ємних аморфних структур - Павленко, А. М.; Усенко, Б. О.; Кошлак, Г. В. (НТУ "ХПІ", 2015)
В статье приведены результаты исследования теплофизических особенностей получения объемных аморфных структур в металлах и сплавах. Рассмотрены особенности процессов тепломассообмена при образовании в расплаве дополнительных активных центров охлаждения, локальных теплостоков для создания внутреннего теплоотвода. Построена математическая модель плавления инокуляторов в расплавах для оптимизации процесса получения массивных аморфных структур, которая позволяет сократить время экспериментальных исследований и материальные ресурсы.

The article presents the results of research of thermophysical peculiarities obtaining volumetric amorphous structures in metals and alloys. This technology differs mainly the realization internal heat removal by means of local heat sink (inoculator). The peculiarities of processes of heat and mass transfer during the formation of in the melt additional active cooling centers, local heat sink to generate internal heat removal. A mathematical model of melting inoculator in melts for optimizing the process of obtaining massive amorphous structures, which allows to reduce time of experimental research and material resources to create massive amorphous structures. Mathematical modeling of processes heat and mass transfer inoculator in melts allows you to identify peculiarities of the technological process, and establish influence inoculator on the degree of amorphization melt. The results of physical experiments are compared with the results of the calculation. The results can be used to analyze the physical regularities and informed choice of technological modes of formation of massive amorphous structures in different metals and alloys. The results provide an effective assessment of the intensity of heat transfer during the casting process, which makes it possible to estimate and predict the ability of alloys to the amorphization of the structure.
The thermophysical peculiarities obtaining of volumetric amorphous structures
Keywords: об'ємні аморфні структури; інокулятори; тепловідведення; плавлення металу